Health-Related Quality of Life among a Sample of Chronic Hepatitis B Patients in AL-Najaf Province /Iraq. - Hanan N. Najaf; Dheyaa J. Kadhim (College of Pharmacy University of Baghdad, 2020)
Abstract The effect of physical and mental health on the feelings of personal welfare are known as health-related quality of life. Infection with hepatitis B virus is a major global health problem. Health-related quality of life was emerged as an important consideration in the care of patients with chronic hepatitis B infection. The aim of the current study was to measure health-related quality of life among a sample of chronic hepatitis B patients in AL-Najaf city/Iraq. The current study was cross-sectional study carried out on (104) already diagnosed chronic viral hepatitis B patients who attended the Gastroenterology and Hepatology Center/Al-Sader Medical City/Najaf during November 2018 to May 2019. In addition, 100 apparently healthy subjects were included as a control group. Health related quality of life was measured using the Arabic version of the Short Form 36. The health-related quality of life of patients with chronic hepatitis B infection was affected by the disease in a highly significant manner where the median scores for all health-related quality of life domains were significantly lower in patients than in controls. Physical functioning score was negatively correlated to age, significantly higher in male patients, significantly higher in high educated patients, significantly higher in single patients, and significantly higher in patients with no children. Role limitation due to physical health score was negatively correlated to age, significantly higher in those with no children. Energy/fatigue score was negatively correlated to age, and significantly higher in male patients. Social functioning score was significantly higher in male patients. Pain score was negatively correlated with age. Physical functioning score was negatively correlated to serum albumin. Social functioning and general health score were negatively correlated to viral load. In conclusion, chronic hepatitis B patients showed significantly lower health-related quality of life scores in various domains compared to healthy control subjects in AL-Najaf province /Iraq.  Key words: Health-Related Quality of Life, Hepatitis B,  Short Form 36, AL-Najaf, Iraq